(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Themost important Buddhist layman in history has been the Emperor Asoka, who ruledmost of India for the middle third of the third century B.C. On the capital ofone of the pillars Asoka erected is beautifully carved a wheel with manyspokes. This representation of the wheel of Dhamma which the Buddha set inmotion is the symbol chosen to adorn the flag of the modern state of India. Thelions on the same capital are on the state seal. Thus India recalls its“righteous ruler.” Asoka is a towering figure for many other reasons too, butwe confine ourselves to his role in Buddhist history. Before Asoka Buddhism hadspread through the northern half of India; but it was his patronage which madeit a world religion. This paper focused about the history of great empror Ashoka.